Review Paper on Total Quality Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
In the current scenario of highly competitive domestic and global business environment, the implementation of the Total Quality Management (TQM) concept has become an important business style and a key survival tool for both the manufacturing and service industries, from large to small, to achieve the business goal and market value. A good number of large-scale companies have embraced TQM for achieving the company's goal and mission there. Negligible Small and Medium Enterprise (SME) units have however implemented TQM. While SMEs play an important role in the country's economic growth and growing population demand, especially in developing countries like India, SMEs are still resistant to adopting TQM. Many Indian SMEs have established suitable QMS (Quality Management System) under customer pressure to obtain ISO 9001 certification leading to quality assurance, but have failed to adopt TQM due to lack of awareness. As such, it has become very important to understand the reasons behind their reluctance in implementing TQM. A number of literatures on the research on the Critical Factors for the successful implementation of TQM and the reasons responsible for the resistance of the SME in implementing TQM are discussed in this review paper. The result will motivate and help them to remove or minimize the barriers of SMEs in implementing TQM to attain business excellence in future research.